Critical Thinking in Context : Final Report for a 1995 National Teaching Development Grant. - Marshall, Lorraine Ann (Committee for the Advancement of University Teaching, 1995)
This is a final report for a 1995 National Teaching Development Grant funded by the Committee for the Advancement of University Teaching. The report details the project, outlining its major objectives and achievements, and suggests applications for the resulting video as a teaching aid in universities.